2022
DOI: 10.1177/2473974x211072791
|View full text |Cite
|
Sign up to set email alerts
|

Telemedicine and Telementoring in Rhinology, Otology, and Laryngology: A Scoping Review

Abstract: Objective Telemedicine and telementoring have had a significant boost across all medical and surgical specialties over the last decade and especially during the COVID-19 pandemic. The aim of this scoping review is to synthesize the current use of telemedicine and telementoring in otorhinolaryngology and head and neck surgery. Data Sources PubMed and Cochrane Library. Review Methods A scoping review search was conducted, which identified 469 articles. Following full-text screening by 2 researchers, 173 articles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 212 publications
0
1
0
Order By: Relevance
“…Including the total number of healthcare visits clearly shows that ENTICES patients were managed in far fewer visits compared with those The overall results showed that 100% would recommend the ENTICES service. Our results are comparable with the literature which all highlight that patient satisfaction for the teleotology experience is high [17].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Including the total number of healthcare visits clearly shows that ENTICES patients were managed in far fewer visits compared with those The overall results showed that 100% would recommend the ENTICES service. Our results are comparable with the literature which all highlight that patient satisfaction for the teleotology experience is high [17].…”
Section: Discussionsupporting
confidence: 90%
“…Cost-efficiency analyses on existing pathways in the literature have shown that telemedicine is more cost-efficient than face-toface [17]. The financial cost of each pathway to the hospital trust has been calculated per consultation.…”
Section: Discussionmentioning
confidence: 99%
“…Although numerous recent national and international studies have delved into the utilisation of eHealth for diagnosis and treatment in otolaryngology care, 13 , 21 34 the current state and attitudes of otolaryngology patients towards the sustained use of digital ICT, even in the post-CoViD-19 pandemic era, remain insufficiently understood. This knowledge gap raises legitimate concerns that must be further addressed.…”
Section: Discussionmentioning
confidence: 99%
“…This review followed the 2018 Preferred Reporting Items for Systematic Reviews and Meta-Analysis-Scoping Review (PRISMA-ScR) guidelines [36][37][38][39], as illustrated in Figure 1. The authors employed a comprehensive search strategy using the Google Scholar search engine in January 2023, which yielded approximately 26,200 results.…”
Section: Literature Profilingmentioning
confidence: 99%